THU0165 Long-Term Radiographic and Patient-Reported Outcomes Based on Clinical Disease Activity Index Responses with Tofacitinib at 6 Months. (15th July 2016) - Strand, V.; Kavanaugh, A.; Kivitz, A.; van der Heijde, D.; Kwok, K.; Akylbekova, E.; Soonasra, A.; Snyder, M.; Connell, C.; Bananis, E.; Smolen, J.
Abstract : Background: Tofacitinib is an oral JAK inhibitor for the treatment of RA. Objectives: This analysis assessed if patients achieving Clinical Disease Activity Index (CDAI) remission (REM) or low disease activity (LDA) at Month 6 had less radiographic progression and improved patient-reported outcomes (PROs) at Month 24 and compared results between tofacitinib and MTX. Methods: ORAL Start (NCT01039688 ) and ORAL Scan (NCT00847613 ) were Phase 3 randomised controlled trials (RCTs) in MTX therapeutically naïve and MTX inadequate response (IR) patients with RA, respectively. In ORAL Start and Scan, patients received tofacitinib 5 or 10 mg twice daily (BID) monotherapy vs MTX monotherapy or tofacitinib 5 or 10 mg BID + MTX vs placebo + MTX, respectively. This was an observed analysis of patients with radiographs at Months 6, 12 and 24, excluding placebo-treated patients in ORAL Scan. Patients were classified according to CDAI responses at Month 6: REM (CDAI ≤2.8); LDA (CDAI >2.8 to ≤10); or incomplete-responders (CDAI >10). Outcomes included the proportion of patients with no radiographic progression (change in modified Total Sharp Score [mTSS] ≤0) and/or HAQ-DI ≤0.5 (defined as normative) at Month 24, and mean changes from baseline in mTSS and HAQ-DI. Results: In ORAL Start, 250, 269 and 98 patients received tofacitinib 5 mg BID, tofacitinib 10 mg BID and MTX, respectively. In ORAL Scan, 193 and 201 patients received tofacitinib 5 and 10 mg BID, respectively. Baseline demographics were generally similar between subpopulations within each RCT; however, incomplete responders generally had higher baseline disease activity. In both ORAL Start and Scan, patients in REM or LDA with tofacitinib at Month 6 were more likely to be radiographic non-progressors and achieve normative HAQ-DI scores at Month 24 (Table ). Tofacitinib-treated patients in REM at Month 6 generally had better HAQ-DI scores at Month 24 than LDA patients. In ORAL Start at Month 6, a higher proportion of tofacitinib- than MTX-treated patients were in REM or LDA (Table ). CDAI incomplete responders receiving tofacitinib had improved HAQ-DI scores and less radiographic progression compared with MTX-treated counterparts. Overall, more tofacitinib-treated patients who achieved REM or LDA were non-progressors or achieved HAQ-DI scores ≤0.5 compared to those treated with MTX. Conclusions: More MTX-naïve or MTX-IR tofacitinib-treated patients achieving CDAI REM or LDA at Month 6 were radiographic non-progressors or achieved normative HAQ DI scores at Month 24, compared with CDAI incomplete responders. In ORAL Start, more tofacitinib-treated than MTX-treated MTX-naïve patients achieved CDAI REM or LDA at Month 6 with better PROs and radiographic outcomes at Month 24. Acknowledgement: Previously presented (Strand V et al. Arthritis Rheumatol 2015; 67 (S10): Abstr 1633) and reproduced with permission from Arthritis Rheumatol. This study was funded by Pfizer Inc. Editorial support was provided by S Johnson of Complete Medical Communications and funded by Pfizer Inc. Disclosure of Interest: V. Strand Grant/research support from: Pfizer Inc, Consultant for: Pfizer Inc, A. Kavanaugh Grant/research support from: Pfizer Inc, A. Kivitz Grant/research support from: Pfizer Inc, Consultant for: Pfizer Inc, Speakers bureau: Pfizer Inc, D. van der Heijde Consultant for: Pfizer Inc, Employee of: Imaging Rheumatology, K. Kwok Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, E. Akylbekova Consultant for: Pfizer Inc, Employee of: Quintiles Inc, A. Soonasra Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, M. Snyder Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Connell Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, E. Bananis Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Smolen Grant/research support from: Pfizer Inc, Consultant for: Pfizer Inc